COMPLEX TREATMENT OF CHRONIC ADENOIDITIS IN CHILDREN - Ikramova F S; Jaxonov O O (PT. Antis International Publisher, 2024)
Background: Chronic adenoiditis in children is a prevalent condition that often leads to significant respiratory issues, including tubar dysfunction and snoring. Specific Background: The Bukhara Regional Children's Multidisciplinary Medical Center provides specialized ENT care, highlighting the need for effective treatment modalities in varying age groups. Knowledge Gap: Traditional therapeutic approaches exhibit limitations in their efficacy, particularly in rapidly alleviating symptoms and restoring normal respiratory function. Aims: This study aims to evaluate the effectiveness of photodynamic therapy (PDT) in comparison to conventional treatments for chronic adenoiditis among children aged 7 months to 11 years. Results: Analysis of 70 pediatric patients revealed that photodynamic therapy significantly improved nasal breathing, reducing snoring and tubar dysfunction five times faster than traditional methods. Additionally, it enhanced anterior active rhinomanometry outcomes, yielding a fourfold increase in total volume flow and a twentyfold reduction in total resistance. Novelty: This investigation is among the first to quantitatively assess the benefits of PDT in pediatric chronic adenoiditis, demonstrating its superior therapeutic efficacy. Implications: The findings suggest that incorporating photodynamic therapy into treatment protocols could offer significant advantages in managing chronic adenoiditis, warranting further exploration and potential integration into clinical practice to improve pediatric respiratory health outcomes.